Lost forever? Ecosystem functional changes occurring after agricultural abandonment and forest recovery in the semiarid Chaco forests - Basualdo, María de los Angeles (2018)
Semiarid forests are worldwide threatened by land use changes, particularly agriculture. However, in some cases, due to particular economic or social processes, agriculture ends and forests may or may not recover to their original state. Using different databases and satellite images integrated into a geographical information system, we located in the central region of the semiarid Chaco forests of Argentina adjacent land use patches of secondary forest (SF), remnant forest (RF) and crops (CP). Using a chronosequence approach, we evaluated changes in the fraction of the photosynthetic active radiation absorbed by the vegetation (FAPAR) between SF and RF and CP, using the enhanced vegetation index (EVI). We evaluated both intra and inter-annual changes in EVI mean (EVImean), EVI maximum (EVImax), EVI minimum (EVImin), and EVI relative range (EVIrr) as descriptors of FAPAR dynamics and analyzed their changes through time (2000 to 2010) and their relation to rainfall. Secondary forests showed higher seasonality and higher EVImean values than RF, but differences disappeared as time since agricultural abandonment increased, suggesting that SF recover their functioning (when compared to RF) after 10 to 15 years. Our results suggest that Chaco's SF have intermediate seasonal patterns in-between RF and CP, as expected by successional theory, and that FAPAR interception by RF appears to be dependent on previous year's precipitation. We found that, although all land uses showed similar precipitation use efficiency (PUE), SF and cropland's productivity were less stable across the years and showed faster increases or decreases compared to RF, depending on precipitation (higher precipitation marginal response- PMR). Our results suggest that at least some aspects of ecosystem functioning can be restored after agricultural abandonment. Future research that combines floristic and structural changes is necessary to fully understand secondary forests regrowth process after agricultural abandonment in the Chaco region.